Elective cesarean section and adverse effects for the neonate (Research, Society and Development, 2023)
Elective cesarean section is the scheduled removal of the baby before the woman goes into labor, due to the inaccuracy of the method of calculating the gestational age, it may present harm to the newborn. This study aimed to contextualize elective cesarean section without plausible indication, identifying the consequences for the neonate. The methodology used was a literature review, searching for national and international articles in databases and electronic journals such as Lilacs, Scielo, Pubmed, Google Scholar and the Virtual Health Library. Among the main results, it was observed that the motivations for this type of delivery go beyond clinical indications, in a sociocultural context in which scheduled surgical delivery is seen by the population as synonymous with quality care. Research shows a direct relationship between prematurity associated with this type of delivery, causing respiratory problems in the newborn; increased length of hospital stay; difficulties inherent to breastfeeding and skin-to-skin contact in the first hour of life. Public policies are extremely important for assertive decision-making in choosing the mode of birth and for preparing women and their families about the parturition scenario, informing them about the risks and benefits of each type of delivery, emphasizing the importance of nursing in this process. It can be concluded that the culture of elective cesarean sections is not a reality that can be easily changed. Therefore, measures for social awareness of the risks of this procedure for the newborn become valid, in order to prevent complications and morbidities.